Design and manufacturing of geotechnical laboratory tools used in physical modeling. Issue 1 (1st January 2019) - Aldefae, Asad H.; Shamkhi, Mohammed S.; Khalaf, Thulfaqar
Abstract: The experimental activities in geotechnical laboratories are highly recommended to be developed annually. Both postgraduate and undergraduate students' research skills are to be improved. In this paper, three main important machines are designed in a geotechnical lab in Wasit University. Uniaxial small shaking table, mechanical pluviator, and pile's model loading machine are fabricated and tested. The shaking table is capable of carrying load up to 1 ton and reproducing a sinusoidal motion containing frequencies up to 10 Hz. The pile's model loading machine is capable of pushing the specimens (pile length up to 60 cm) in the granular soil in very-low-speed rate (i.e. 0.3mm/min), whereas the designed pluviator catches the density range between 28% and 73%. The measured acceleration response and the amplification noticed during wave propagation to the model surface shaking showed great results, and they were consistent with historical records (i.e. approximately 1.6). Great repeatability and highest degree of uniformity are also observed for the prepared models of sandy layers using the new mechanical pluviator from the measured cone resistant (i.e. cone penetration test results for prepared cohesionless specimens). It was also noticed that the design used for the shaking table gave very well prediction for the input motion, confirming that side walls of the container were not strongly affected on the laterally reflected wave.